Design Of Horizontal Type Of Wind Turbine On A Highrise Building - wahirom - -; Nofirman - -; Prayudi - (KILAT, 2021)
In making a horizontal type wind turbine, of course, it is necessary to analyze it in depth, one of which is by predicting the production of wind energy produced by the wind turbine to estimate the wind power in the wind turbine which will later be applied. Wind energy sources that are commonly used are located in rural areas, fields and even there is such a large amount of energy that it is sometimes difficult to reach the power grid and other large areas including the roofs of high-rise buildings. There are many analytical models in wind energy estimation, one of which is often done by many researchers, namely by using the Weibull distribution method. From the measurement results that as many as 1516.37 kWh with a 1 kW wind turbine with a radius of 1 meter (capacity factor 30.09%). Modeling wind turbine blades with NACA 4412 using Qblade software to determine the torsional angle of the blade to be applied so that it is obtained that the torsion angle from the base and The tip of the blade has a tilt angle of 19.05◦ to 6.96° with a maximum Cp of 0.5 this is a pretty good value in designing wind turbine blades.